2008
DOI: 10.1186/1471-2180-8-207
|View full text |Cite
|
Sign up to set email alerts
|

The expression and antigenicity of a truncated spike-nucleocapsid fusion protein of severe acute respiratory syndrome-associated coronavirus

Abstract: BackgroundIn the absence of effective drugs, controlling SARS relies on the rapid identification of cases and appropriate management of the close contacts, or effective vaccines for SARS. Therefore, developing specific and sensitive laboratory tests for SARS as well as effective vaccines are necessary for national authorities.ResultsGenes encoding truncated nucleocapsid (N) and spike (S) proteins of SARSCoV were cloned into the expression vector pQE30 and fusionally expressed in Escherichia coli M15. The fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…MERS-CoV patients were observed to have low-level crossreactivity to SARS-CoV 88 and in one study HCoV-HKU1 N protein 76 . Because of this cross-reactivity, researchers have developed diagnostic assays with truncated SARS-CoV S, N, and M proteins [91][92][93][94] . A study with longitudinal follow-up suggests that the titers may indeed reflect stimulation of preexisting antibodies from past infections as avidity of IgG Fig.…”
Section: Not Reportedmentioning
confidence: 99%
“…MERS-CoV patients were observed to have low-level crossreactivity to SARS-CoV 88 and in one study HCoV-HKU1 N protein 76 . Because of this cross-reactivity, researchers have developed diagnostic assays with truncated SARS-CoV S, N, and M proteins [91][92][93][94] . A study with longitudinal follow-up suggests that the titers may indeed reflect stimulation of preexisting antibodies from past infections as avidity of IgG Fig.…”
Section: Not Reportedmentioning
confidence: 99%
“…MERS-CoV patients were observed to have low-level cross-reactivity to SARS-CoV-1 77 and in one study HCoV-HKU1 N protein 79 . Because of this cross-reactivity, researchers have developed diagnostic assays with truncated SARS-CoV-1 S, N, and M proteins [81][82][83][84] . See Figure 5 for associations between homologous and heterologous titers.…”
Section: Emerging Hcovs Can Induce Cross-reactive Binding Antibodiesmentioning
confidence: 99%
“…The spike protein of HCoV-HKU1, HCoV-NL63, HCoV-229E, and SARS-CoV-2, analyzed by a pairwise similarity plot, showed that HCoV-HKU1 had the highest similarity in all spike regions to the SARS-CoV-2 spike, compared with HCoV-229E and HCoV-NL63 [ 43 ]. SARS-CoV-1 was reported to share epitopes with HCoV-OC43, and weak cross-reactions were also found with HCoV-229E [ 44 , 45 , 46 ]. Che and colleagues [ 45 ] found that sera from SARS-CoV-1 showed a several fold increase in antibody titers against HCoV-229E and HCoV-OC43 compared to controls.…”
Section: Evidence Of Cross-reactivity Towards Hcov Mers-cov Sars-cov-...mentioning
confidence: 99%